Hip-inspired implant for revision of failed reverse shoulder arthroplasty with severe glenoid bone loss. (April 2014) - Uri, Ofir; Bayley, Ian; Lambert, Simon
<x xml:space="preserve">Abstract</x> Background and purpose — Glenoid reconstruction and inverted glenoid re-implantation is strongly advocated in revisions of failed reverse shoulder arthroplasty (RSA). Nevertheless, severe glenoid deficiency may preclude glenoid reconstruction and may dictate less favorable solutions, such as conversion to hemiarthropasty or resection arthropasty. The CAD/CAM shoulder (Stanmore Implants, Elstree, UK), a hip arthroplasty-inspired implant, may facilitate glenoid component fixation in these challenging revisions where glenoid reconstruction is not feasible. We questioned (1) whether revision arthroplasty with the CAD/CAM shoulder would alleviate pain and improve shoulder function in patients with failed RSA, not amenable to glenoid reconstruction, (2) whether the CAD/CAM hip-inspired glenoid shell would enable secure and durable glenoid component fixation in these challenging revisions. Patients and methods — 11 patients with failed RSAs and unreconstructable glenoids underwent revision with the CAD/CAM shoulder and were followed-up for mean 35 (28–42) months. Clinical outcomes included the Oxford shoulder score, subjective shoulder value, pain rating, physical examination, and shoulder radiographs. Results — The average Oxford shoulder score and subjective shoulder value improved statistically significantly after the revision from 50 to 33 points and from 17% to 48% respectively. Pain rating at rest and during activity improved significantly from 5.3 to 2.3 and from 8.1 to 3.8 respectively. Active forward flexion increased from 25 to 54 degrees and external rotation increased from 9 to 21 degrees. 4 patients required reoperation for postoperative complications. No cases of glenoid loosening occurred. Interpretation — The CAD/CAM shoulder offers an alternative solution for the treatment of failed RSA that is not amenable to glenoid reconstruction.